The Effectiveness of Practicum Method Assisted with PHeT Media on Character and Learning Outcomes of IPA - Bayu Indra Pratama; Sri Sukasih (Postgraduate, University of Mataram, 2024)
This study aimed to evaluate the effectiveness of a PhET-assisted practical method on the character development and academic achievement of IPA students at SDN Kepandean 03. A quasi-experimental design with a pretest-posttest control group was employed. The sample consisted of 28 students in the experimental group and 28 students in the control group, randomly selected from classes VA and VB. The results indicated that the experimental group, which utilized the PhET-assisted practical method, exhibited significant improvements in both character development (posttest mean: 83.75) and academic achievement (posttest mean: 85.11), compared to the control group (character: 77.71, academic achievement: 74.89). These findings suggest that the PhET-assisted practical method is an effective approach for enhancing students' character and academic performance in IPA.